SAT0277 Has Shoulder Ultrasonography Got A Predictive Value in Polymialgia Rheumatica?. (10th June 2014) - Miceli, M.C.; Petricca, L.; Peluso, G.; Alivernini, S.; Gremese, E.; Privitera, R.; Zoli, A.; Ferraccioli, G.
Abstract : Background: Polymyalgia rheumatica (PMR) is an inflammatory condition characterized by aching and morning stiffness in the shoulders, hip girdle, and neck. The initial goal of therapy is to rapidly achieve symptomatic control using a relatively low dose of glucocorticoids although most patients require long duration treatment and relapses are common with tapering dosage. Recently musculoskeletal ultrasound (MUS) has been proposed as part of PMR classification criteria. Objectives: To assess if a positive MUS pattern of the shoulder (presence of subdeltoid bursitis and/or biceps tenosynovitis) at the diagnosis may represent a predictive marker of response to standard therapy at after 12 months follow-up and may correlate with an higher maintenance dosage of steroid at 6 and 12 months follow-up. Methods: 66 consecutive outpatients (51 (77, 3%) female) with PMR underwent a shoulder MUS at the time of diagnosis before starting therapy, and after 12 months follow-up. Clinical and laboratory assessment of age, girdle pain, 44 swollen and tender joint count, inflammatory markers was performed. Glucocorticoids at low doses were the mainstay of treatment. Clinical remission was defined as lack of girdle pain and as levels of eritrosedimentation rate (ESR)≤40 mm/h and c-reactive protein (CRP)≤4 mg/l. Results: At the study entry, PMR patients had a mean age of 72±6.9 years. All patients presented aching shoulder and 16 (24, 2%) had peripheral arthritis. A positive MUS pattern of the shoulder was present in 46 (69, 7%) patients of whom 33 (71, 8%) patients became negative after 12 months follow-up. 13 (28, 2%) patients remains still positive at MUS evaluation after 12 months. All patients rapidly achieve a symptomatic persistent control due to prednisone at the initial mean dosage of 16, 29±8, 19mg/die of prednisone gradually tapered until a maintenance dose. At 6 months follow-up, 30 (45, 5%) patients were treated with prednisone >5 mg/die, of whom 22 (73.3%) had positive MUS pattern and 8 (26.7%) had negative MUS pattern at the study entry. Among the general cohort, after 12 months follow-up, 7 (10, 6%) patients were treated with prednisone >5 mg/die, of whom 3 (42.8%) showed positive and 4 (57.2%) a negative MUS pattern at baseline. No significant difference was found for the mean dosage of steroid at 6 and 12 months follow-up (p=0, 37 and p=0, 35 respectively) comparing PMR patients with positive and negative MUS at the study entry. Moreover no difference was found in the remission rate between patients with positive and negative MUS pattern at the baseline (50, 0% of MUS positive patients vs 45, 0% of MUS negative patients in disease remission, p=0, 46). Conclusions: In conclusion in PMR patients, ultrasonographic presence of shoulder bursitis or tenosynovitis at the time of diagnosis is not a predicting marker of higher corticosteroid maintenance dose in the long-term glucocorticoid therapy nor of clinical remission after 12 month of therapy. Normalization of the initial ultrasonographic changes in patients with persistent control of the disease suggests that MUS can add specificity to the diagnosis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5028